Studi Komparasi Layanan Smart City Antara Kota Semarang dan Kota Malang - Ajniver Hamnur Zebua; Aulia Surya Pertiwi; Ilmi Sulistiati Anisa; Muhammad Thoriq Ramadhani; Tria Rama Nabila; Irvan Arif Kurniawan (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
Aulia Surya Pertiwi1, Ilmi Sulistiati Anisa2, Muhammad Thoriq Ramadhan3, Siti Wahyuni Rahmawati4, Tria Rama Nabila5, Irvan Arif Kurniawan6 Universitas Islam Syekh-Yusuf Tangerang, Fakultas Ilmu Sosial dan politik. Program studi Ilmu Administrasi Negara auliasryprtwi@gmail.com1, ilmysulistiatianisa@gmail.com2, rthoriq23@gmail.com3, yunnir016@gmail.com4, trianabila112@gmail.com5, iakurniawan@unis.ac.id6 ABSTRACT. A smart city is one that includes contemporary infrastructure and transportation systems, Additionally to human and social capital, create high-quality, long-term economic growth. The idea of the